1996
DOI: 10.1016/s0194-5998(96)70244-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of eosinophil cationic protein and myeloperoxidase from chronic middle ear effusion in patients with allergy and/or acute infection

Abstract: Middle ear eosinophil cationic protein may be used as a marker of related allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…In allergic asthma and in allergic rhinitis eosinophils dominate. The present study shows in OME a covariation between the occurrence of eosinophils and neutrophils (Table 1) and supports the findings in effusions described by Hurst and Venge [12]. A possible explanation for this may be a different role for bacteria or viruses in OME as Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In allergic asthma and in allergic rhinitis eosinophils dominate. The present study shows in OME a covariation between the occurrence of eosinophils and neutrophils (Table 1) and supports the findings in effusions described by Hurst and Venge [12]. A possible explanation for this may be a different role for bacteria or viruses in OME as Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The use of specific antibodies to granule proteins in eosinophils and neutrophils makes it possible to demonstrate the presence of these cells and their products with greater certainty than is possible with purely morphological techniques, in particular when the cells are degranulating. Hurst and Venge [22] demonstrated, using immunological techniques, the presence of ECP in effusion from OME patients, and in a later study [12] confirmed this finding and also showed the presence of MPO in such effusions. In a recent pilot study, Hurst and Fredens [13] used polyclonal antibodies to demonstrate the presence of ECP positive cells in the lining of the middle ear of OME patients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…An increased MPO concentration is an indirect, but clear indication of MPO release by an inflammatory process. MPO, as a marker of inflammation, has been measured to distinguish otitis media, chronic sinusitis, chronic bronchitis and peritonitis of bacterial origin [10][11][12], in which excellent correlations have been observed with levels of IL-8, a cytokine involved not only in chemotaxis, but also in neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
“…MPO and reduced nicotinamide-adenine dinucleotide phosphate (NADP-H) oxidase are the main proteins that participate in oxidative-type microbicidal activity [9]. Increased concentrations of MPO have been reported in various inflammatory processes [10][11][12]. The authors previously detected higher levels of pleuralfluid MPO in complicated bacterial effusions than in noninfective effusions [13].…”
mentioning
confidence: 99%